When the "Other" Shares Your Faith: The Case of Sicily and al-Andalus in Ibn Ḥawqal's Kitāb ṣūrat al-arḍ with a New Translation - Grasso, Valentina A. (Journal of medieval religious cultures, 2025)
“No doctrine is comparable in any other country, and no heresy nor belief in any other religion.” According to Ibn Ḥawqal (d. after 978), an Arab geographer raised in Iraq, the inhabitants of tenth-century Sicily are among the most vain, most ignorant, and most xenophobic people on earth. This article explores the articulation of otherness in the Kitāb ṣūrat al-arḍ, a text Ibn Ḥawqal wrote after his sojourn on the island in 973, which is here included in a new English translation. The geographer’s description of Sicily is embedded in a moralizing discourse that veers toward grotesque. His rejection of Sicily’s distance from the paradigm of a “good” Muslim country upholds the island’s “untranslatability” as an unforgivable weakness and a sign of moral degradation. Nonetheless, his account of Palermo and its surroundings provides crucial historical information on the island’s economic and geopolitical situation. Moreover, it offers an enlightening account for the study of interfaith dialogue, “otherness,” and “Islamization.” Accordingly, this article features the first English translation of the section on al-Andalus as it is crucial to evaluate Ibn Ḥawqal’s critique of Sicily, as both Mediterranean territories were conquered by the Muslims not long before Ibn Hawqal’s travels.